MELIHAT KEMUNGKINAN DILAKUKANNYA RESTORATIVE JUSTICE BERBASIS PENJARA DI INDONESIA - Wibawa, Akbar Setia (Universitas Ekasakti, 2023)
The practice of restorative justice has been carried out in response to the damage caused by crime. This can be seen from the increasing number of restorative justice that appears at various stages of the criminal justice process. Nevertheless, prison based restorative justice programs in Indonesia has not been implemented. Restorative justice programs in the context of a correction system can be useful, especially if rehabilitation is one of the main goals of imprisonment. Through this article, the author conducts a literature review on journal articles, books, and regulations related to prison based restorative justice. The results show that restorative justice in prisons can be useful for prisoners, victims, society, prisons, and officers. It contributes to the process of social reintegration which is the main goal of correctional system. Even so, there are also obstacles that must be faced such as the need for a lot of resources, the potential to intimidate victims, tight schedules in prison, and the possibility of inmates being transferred at any time. In the end, the conclusion of this article brings us to an understanding of the importance of implementing prison-based restorative justice programs in Indonesia.